Studies on Trypanosoma rangeli Tejera, 1920: IX. Course of infection in different stages of Rhodnius prolixus - Añez,N. (1987)
Frequent individual observations od different stages of Rhodnius prolixus exposed to Trypanosoma rangeli, revealed a higher susceptibility to infection in the bugs exposed during the two first instars. The mortality rate in infected bugs was significantly higher than in controls, indicating that the parasite was responsible for the majority of deaths. An analysis of the mortality distribution, per instar, is presented. Statistical analysis of deaths among the different infected instars, showed that T. rangeli produces its pathological effect in any stage of R. prolixus independently of its susceptibility to the parasite. The survival to adult decreased in all the infected instar bugs. A significant longer time to reach the adult stage was observed in the infected bugs when compared with controls, excepting for specimens exposed in the third instar. The epidemiological significance of the present results is discussed.